Evaluation of the Antimicrobial Potential of Pleurotus ostreatus Extracts (Journal of Scientific Research, 2025)
Antimicrobial activity of Pleurotus ostreatus was studied in vitro using its aqueous and methanolic extracts, against nine human pathogenic bacteria (MTCC cultures) such as Bacillus subtilis, Listeria monocytogenes, Staphylococcus aureus, Streptococcus pneumoniae - Gram positive bacteria; Escherichia coli, Enterobacter aerogenes, Klebsiella pneumoniae, Proteus vulgaris, Salmonella enterica ser. typhi and Shigella flexneri - Gram negative bacteria. Antifungal potential was screened against phytopathogenic fungi like Alternaria sp., Aspergillus sp., Fusarium sp. and Helminthosporium sp. The P. ostreatus aqueous extract failed to show growth inhibitory effect against any of the human pathogenic bacteria or phytopathogenic fungi studied. The P. ostreatus methanolic extract exhibited significant inhibition of all the bacteria tested at higher concentrations of 2000, 3000, 4000 and 5000 ppm. But, even P. ostreatus methanolic extract could not inhibit the growth of phytopathogenic fungi studied, at any of the concentrations screened. P. ostreatus methanolic extract was found to have phytochemicals such as alkaloids, flavonoids, phenols, saponins, steroids, tannins, and terpenoids. The results of present studies reveal the antibacterial potential of Pleurotus ostreatus, which could be further evaluated to obtain potent antibacterial bioactive principles for new drug development.